Neuropathies - Guillain-Barré syndrome: rehabilitation - Tuacek, Tatiana Amadeo; Tsukimoto, Gracinda Rodrigues; Figliolia, Carmen Silvia; Cardoso, Maiara Celina de Carvalho; Tsukimoto, Denise Rodrigues; Rosa, Chennyfer Dobbins Paes da; Imamura, Marta; Battistella, Linamara Rizzo (Acta Fisiátrica, 2013)
Articles in the MedLine (PubMed) database and other research sources were reviewed, with no age limit. The search strategy used was based on structured questions in the P.I.C.O. format (from the initials: Patient, Intervention, Control and Outcome).